2013
DOI: 10.1007/s10665-013-9651-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interfacial slip on the stability of liquid two-layer polymer films

Abstract: In this work we derive systems of coupled thin-film equations for immiscible liquid polymer layers on a solid substrate. We take into account slip between liquids and solids and also slip between both liquids. On the scale of tens of nanometres such two-layer systems are susceptible to instability and may rupture and dewet due to intermolecular forces. The stability of the two-layer system and its significant dependence on the order of magnitude of slip is investigated via these thin-film models. With weak sli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…corresponding to the weak-slip conditions at the both interfaces. As it was shown recently in [14] the latter model incorporates both the no-slip and the Navier-slip models (1.5),(1.6) as limiting cases as the slip lengths b, b 1 tend simultaneously to zero or infinity, respectively. One needs to point out that we obtained a slight difference between the weak formulations in the no-slip and Navier-slip cases (compare Theorems 2.1 and 4.1).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…corresponding to the weak-slip conditions at the both interfaces. As it was shown recently in [14] the latter model incorporates both the no-slip and the Navier-slip models (1.5),(1.6) as limiting cases as the slip lengths b, b 1 tend simultaneously to zero or infinity, respectively. One needs to point out that we obtained a slight difference between the weak formulations in the no-slip and Navier-slip cases (compare Theorems 2.1 and 4.1).…”
Section: Conclusion and Discussionmentioning
confidence: 90%
“…The mobility function has the form M (h) = h 3 or M (h) = bh 2 for the no-slip or Navier-slip conditions considered at the solid-liquid interface, respectively, where b > 0 denotes the slip-length parameter. Recently, this model was generalized to a coupled lubrication system describing evolution of a layered system of two viscous, immiscible, nanoscopic Newtonian fluids evolving on a solid substrate [1,9,14] and subsequently analysed in [2,13,14,16,18]. The latter system can be stated in the form:…”
Section: Introductionmentioning
confidence: 99%
“…2004; Merabia & Bonet Avalos 2008; Jachalski et al. 2014). Liquid–liquid interfaces, in particular those between two polymers, often exhibit apparent slip (de Gennes 1989; Brochard-Wyart & de Gennes 1990; de Gennes & Brochard-Wyart 1990), and have been studied with molecular dynamics simulations (Koplik & Banavar 2006; Razavi, Koplik & Kretzschmar 2014; Poesio, Damone & Matar 2017) and experiments (Lee et al.…”
Section: Introductionmentioning
confidence: 99%
“…2011; Jachalski et al. 2014). The capillary-levelling technique was applied to a variety of geometries and configurations, which range from imprinted nano-patterns (Stillwagon & Larson 1988; Buck et al.…”
Section: Introductionmentioning
confidence: 99%
“…The instabilities of the thin polymer bilayers are generally governed by the thermodynamic forces. However, some recent studies [36][37][38][39][40][41][42][43][44] have indicated that kinetic forces also greatly inuence the instability of the thin polymer bilayer, as a result the instability could become a kinetically controlled one. Bandyopadhyay et al 36 have shown that a marked decrease in the viscosity of the upper layer increases the rate of deformation of the upper interface, causing the instability shiing back to the upper interface.…”
Section: Introductionmentioning
confidence: 99%